14: USING UNDERGRADUATES TO PREPARE INTERNATIONAL TEACHING ASSISTANTS FOR THE AMERICAN CLASSROOM. (10th October 2017) - Christian, Warren E.; Rybarczyk, Brian J.
Abstract : This chapter describes how undergraduates may be used in the training of international teaching assistants (ITAs) in three ways: as conversation partners, classroom consultants, and guest instructors. Increasing the contact between undergraduates and international graduate students before they meet in the classroom as students and instructors can benefit each group. After a brief review of the literature that explores the challenges ITAs face in the American university classroom, we describe the roles that undergraduates may perform in training ITAs, explain the benefits to both ITAs and undergraduates, and provide a list of best practices for including undergraduates in ITA training.